Recast on Speaking Ability as Observed from Levels of Anxiety - Riezky Amalia (Language-Edu, 2019)
AbstractThis research is conducted to investigate recast on speaking ability as observed from levels of anxiety. This research employed quasi-experimental research. The instrument used in the form of the questionnaire and the speaking test. The data were analyzed using SPSS 24. This research aims to examine; whether there is the improvement of the experimental group on the post-test scores; whether there is a difference in students’ speaking ability with high and low anxiety. Therefore, between the high and low anxiety of the students have a different speaking ability; whether there is any difference between high and low anxiety through recast and the conventional technique. Thus, between the high and low anxiety of the students have a different significant result; and whether there is any interaction between recast and anxiety. Thus, between the high and low anxiety of the students have no interaction with each other on the recast. This research employed analysis of variance (ANOVA) in this case using two-way ANOVA. The p-value (Sig.) is lower than the level of significance α=.05 which means that  H0 is rejected. In other words, there is a difference in speaking ability between recast and the conventional technique. Keywords: recast, anxiety, and speaking ability